Influences of Smoking Status on Effectiveness of Cytochrome P450 Enzyme System Metabolized Medications in Reducing In-Hospital Death in 14 658 Patients With Acute Myocardial Infarction: Data From CPACS-3 Study. (September 2020) - Li, Min; Feng, Lin; Li, Xian; Gao, Runlin; Wu, Yangfeng
Background: The benefit of cytochrome P450 (CYP450) enzyme system metabolized medications, especially clopidogrel, was reported more pronounced in smoking than nonsmoking patients, but limited evidence was available from Asian patients. We analyzed data from a large registry-based study of Chinese patients with acute myocardial infarction (AMI) to understand if the above finding could be reproduced. Methods: A total of 14 658 patients with AMI were prospectively recruited from 101 hospitals across China. Generalized estimating equation was applied to assess the association between CYP450 enzyme system metabolized medications (clopidogrel, statins, calcium channel blockers) and in-hospital death in smoking and nonsmoking patients, separately, adjusting for hospital clustering effects and propensity score of using the medication in question. Results: There were 86%, 93%, and 10% of study patients who received clopidogrel, statins, and calcium channel blockers during the hospitalization. Compared with patients not receiving clopidogrel, patients receiving the drug had a significantly lower risk of in-hospital death (adjusted relative risk [RR] = 0.61, 95% confidence interval [CI]: 0.40-0.91) in current smokers but an insignificant lower risk (adjusted RR = 0.85, 95% CI: 0.71-1.01) in nonsmokers, and the P for interaction was <.01. The corresponding adjusted RR was 0.45 (95% CI: 0.24-0.86) in current smokers and 0.94 (95% CI: 0.68-1.29) in nonsmokers ( P for interaction <.01) for statins use and 1.00 (95% CI: 0.53-1.89) in current smokers and 0.66 (95% CI: 0.48-0.90) in nonsmokers ( P for interaction = .23) for calcium channel blockers use. Conclusions: Our study in a large cohort of Chinese patients with AMI found that the treatment effect in reducing risk of in-hospital death was significantly larger in smokers than in nonsmokers as for clopidogrel and statins but not for calcium channel blockers.